Reversing inflammatory diseases via trained immunity: mechanisms, challenges, and prospects - Xu, Wanli; Guo, Zhilin; Xu, Tingyun; Chen, Junjie; Chen, Leyi; Xu, Wenan (Frontiers in Immunology, 2025)
Chronic inflammatory diseases are widespread and often accompanied by comorbidities, making treatment challenging. Current immunosuppressive and anti-inflammatory therapies have limited efficacy and significant side effects, and are insufficient to address the complexity of coexisting conditions. This review explores recent advances in innate immune memory, also known as trained immunity, and its potential role in inflammatory diseases. We hypothesize that targeting the regulatory mechanisms of trained immunity may lead to novel therapeutic strategies that more effectively control inflammation and improve disease outcomes. Finally, we highlight that the interplay between trained immunity and inflammatory diseases remains incompletely understood, and further research is needed to elucidate its mechanisms and clinical translational potential.